Development and validation of the BMQ-AIR©: a screening tool for assessing patients' treatment beliefs about switching to anti-inflammatory reliever (AIR) therapy - Holly Foot; Holly Foot; Amy Hai Yan Chan; Amy Hai Yan Chan; Rob Horne; Rob Horne (Frontiers Media S.A., 2024)
IntroductionDespite anti-inflammatory reliever (AIR) therapy now being the preferred treatment choice across all severities of asthma, many patients are still "attached" to their short-acting beta2-agonist (SABA) reliever, believing this to be the best way to control their asthma. To encourage individuals to switch to AIR, it is important to first identify the beliefs that patients hold about AIR.ObjectiveThe aim of this paper was to describe the initial development and validation of the BMQ-AIR©, a six-item screening tool which assesses and identifies patients' treatment beliefs about switching to AIR therapy.MethodsStatements were identified from the primary literature that assessed patients' perceptions of AIR therapy and adapted from the Beliefs about Medicines Questionnaire (BMQ). Internal reliability was examined using Cronbach's alpha coefficient. Construct validity was evaluated by comparing scores on BMQ-AIR© with a validated measure of medication adherence and SABA beliefs.ResultsA total of 446 participants completed the online survey. The BMQ-AIR© contained two subscales with three items each. Both the Necessity and Concerns subscales demonstrated good internal reliability, with Cronbach's α-values of 0.70 and 0.69, respectively. Both subscales were negatively correlated with self-report inhaled corticosteroid adherence (Necessity: r = −0.28, p < 0.0001; Concerns: r = −0.28, p < 0.0001) and positively correlated with SRQ scores (Necessity: r = 0.51, p < 0.0001; Concerns: r = 0.44, p < 0.0001).ConclusionPreliminary findings indicate that BMQ-AIR© demonstrates satisfactory reliability and validity. BMQ-AIR© is a promising tool that may help tailor interventions to an individual's specific beliefs and barriers to switching to better support individuals in stopping SABA and initiating AIR therapy.